Lithium-rich manganese-based material with spinel-coated Na2SeO3 structure and preparation method thereof
By mixing sodium selenite with lithium-rich manganese-based positive electrode material and calcining it to form a spinel @Na2SeO3 structure, the problem of poor electrochemical performance of positive electrode materials in the prior art is solved and a higher level is achieved discharge specific capacity, initial Coulomb efficiency and cycle stability.
Patent Information
- Application Number
- CN202411574055.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the prior art, the electrochemical performance of lithium-rich manganese-based cathode materials is poor, mainly due to irreversible oxygen precipitation, resulting in structural distortion and irreversible capacity loss.
Sodium selenite is mixed with lithium-rich manganese-based positive electrode material and calcined under argon environment to form a lithium-rich manganese-based material with spinel @Na2SeO3 structure. This method initiates the reduction of Mn4+ to Mn3+ through the Se4+ reduction reaction on the Na2SeO3 surface, thereby inducing the formation of a spinel structure and enhancing the structural stability of the material surface.
Through the synergistic effect of the Na2SeO3 coating and the in-situ spinel phase, it effectively inhibits unstable oxygen release, protects the active material, improves the transmission efficiency of lithium ions, and significantly improves the electrochemical performance of the material, including discharge specific capacity, initial Coulomb efficiency and cyclic stability.
Smart Images

Figure CN119409236A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and more particularly, to a lithium-rich manganese-based material having a spinel@Na2SeO3 structure and a preparation method thereof. Background Art
[0002] With the rapid development of electric vehicles and energy storage devices, electrochemical energy storage batteries with high energy density and low cost, such as lithium-ion batteries (LIBs), have attracted increasing attention. Lithium-rich manganese-based materials (xLi2MnO3·(1-x)LiTMO2, 0 < x < 1, TM = Mn, Co, Ni, etc.) are considered to be one of the most promising cathode materials due to their specific capacity exceeding 250 mAh g -1 . Generally, the high specific capacity of lithium-rich manganese-based oxide materials not only comes from the redox reaction of transition metal ions in the low voltage range, but also may come from the redox reaction of oxygen anions at high voltages. Irreversible oxygen evolution inevitably brings certain structural distortion and irreversible capacity loss, resulting in extremely low ICE and electrochemical performance.
[0003] Since the release of unstable oxygen always occurs at the electrode / electrolyte interface and is accompanied by various side reactions, surface coating has become one of the most effective ways to improve the electrochemical performance of electrode materials. The coated surface can serve as a protective layer for the active material, reducing irreversible capacity loss. At the same time, the presence of oxygen vacancies and spinel phases on the surface helps to inhibit irreversible oxygen release and enhance lithium ion diffusion.
[0004] In the field of lithium-ion batteries, there are many substances that can be used for surface coating. The coating material should have the advantages of high Li + mobility and good structural stability. Generally, metal oxides, fluorides, metal phosphates, carbon materials, and polymer conductive materials are used as surface coating materials to improve the electrochemical performance of lithium-rich materials. However, the most fundamental problems, namely the irreversible loss of lattice oxygen and the side reactions between the electrode / electrolyte interface, have not been solved. Uniform Se 6+ doping can improve the crystallinity of Li2MnO3, thereby making the atomic arrangement in the transition metal layer of the lithium-rich manganese-based cathode material more orderly. However, unfortunately, this modification method has not significantly improved the electrochemical performance. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a lithium-rich manganese-based material having a spinel@Na2SeO3 structure and a preparation method thereof to solve the problem of poor electrochemical performance of the cathode material in the prior art.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] The present invention provides a method for preparing a lithium-rich manganese-based material with a spinel @Na2SeO3 structure. The lithium-rich manganese-based positive electrode material is mixed with sodium selenite and ground, and then calcined under an argon environment to obtain the lithium-rich manganese-based material with the spinel @Na2SeO3 structure.
[0008] Based on the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the calcination temperature is 330° C. to 370° C., and the calcination time is 2 to 4 hours.
[0010] Furthermore, based on the total mass after mixing as 100%, the mass percentage of the sodium selenite is 1wt% to 4wt%.
[0011] Furthermore, the lithium-rich manganese-based positive electrode material is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 material.
[0012] Furthermore, the Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 The preparation method of O2 material is co-precipitation-high temperature solid phase method.
[0013] Further, the coprecipitation-high temperature solid phase method comprises the following steps:
[0014] S1, preparation containing Mn 2+ 、Ni 2+ 、Co 2+ A mixed sulfate solution, a Na2CO3 solution and an ammonium bicarbonate aqueous solution; wherein the Mn 2+ 、Ni 2+ 、Co 2+ The molar ratio is 54:13:13, the total cation concentration is 2 mol / L, the concentration of the Na2CO3 solution is 2 mol / L, and the concentration of the ammonium bicarbonate aqueous solution is 0.12 mol / L;
[0015] S2, injecting the mixed sulfate solution and the Na2CO3 solution into the preheated ammonium bicarbonate aqueous solution at the same time, stirring and reacting, and after the reaction is completed, standing and aging to obtain a product; the feed rate of the mixed sulfate solution and the Na2CO3 solution is 0.5mL / min; the reaction time is 15 to 17h;
[0016] S3, filtering, separating, washing and drying the product in sequence to obtain a carbonate precursor powder;
[0017] S4, mixing and grinding the precursor powder and lithium carbonate, wherein the molar ratio of the precursor powder to the lithium carbonate is 1:1.35; then pre-calcining and high-temperature calcining are performed in sequence to obtain the Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 material; the pre-sintering temperature is 550℃~650℃, the time is 4~6h, the high temperature calcining temperature is 850~950℃, the time is 10~12h.
[0018] Furthermore, in step S2, the preheating temperature is 53°C to 57°C.
[0019] Furthermore, in step S2, the temperature of the static aging is 55° C. and the time is 12 hours.
[0020] The present invention also provides a lithium-rich manganese-based material with a spinel@Na2SeO3 structure, which is prepared by the above method.
[0021] The present invention also provides a lithium ion battery prepared using the lithium-rich manganese-based material as described above.
[0022] The beneficial effects of the present invention are:
[0023] (1) The preparation method of the lithium-rich manganese-based material having a spinel @Na2SeO3 structure of the present invention comprises mixing sodium selenite with a lithium-rich manganese-based positive electrode material and calcining the mixture to make the Se on the surface of Na2SeO3 4+ A reduction reaction occurs, initiating the Mn 4+ Reduced to Mn 3+ , Mn 3+ The appearance of induced the formation of a layer of spinel structure on the surface of the material, and finally a lithium-rich manganese-based material with spinel@Na2SeO3 structure was obtained;
[0024] (2) The preparation method of the lithium-rich manganese-based material having a spinel@Na2SeO3 structure of the present invention, the Na2SeO3 coating layer can generate abundant oxygen vacancies on the surface of the material, effectively inhibiting the unstable oxygen release during the cycle and protecting the active material from corrosion by the electrolyte; as an in-situ spinel phase, it can provide a three-dimensional lithium ion transmission channel, thereby effectively accelerating the transmission of lithium ions;
[0025] (3) The preparation method of the lithium-rich manganese-based material having a spinel@Na2SeO3 structure of the present invention has simple steps, mild reaction conditions and low preparation cost;
[0026] (4) The lithium-rich manganese-based material having a spinel@Na2SeO3 structure of the present invention, Na2SeO3 coating can enhance the structural stability of the material surface, thereby reducing structural rearrangement during charging and discharging;
[0027] (5) The lithium-rich manganese-based material with a spinel@Na2SeO3 structure of the present invention has better electrochemical properties, and its discharge specific capacity and initial coulombic efficiency are effectively improved; the capacity retention rate after 200 cycles at 0.5C and 1C rates, the specific capacity at 10C rate, and the voltage drop after 200 cycles are improved to varying degrees. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The preparation method of the lithium-rich manganese-based material with a spinel @Na2SeO3 structure of the present invention, the lattice structure analysis diagram of Example 2, Figure 1 a is the XRD pattern of each sample. Figure 1 b in the figure is the Raman spectrum of each sample;
[0029] Figure 2 The preparation method of the lithium-rich manganese-based material with spinel @Na2SeO3 structure of the present invention, the microscopic morphology analysis diagram of Example 3, Figure 2 a and b are SEM images of NSO-0. Figure 2 c and d are SEM images of NSO-1%. Figure 2 Figures e and f are SEM images of NSO-2%. Figure 2 Figures g and h are SEM images of NSO-3%. Figure 2 The i and j in the figure are SEM images of NSO-4%. Figure 2 k is the EDS mapping of NSO-3%, Figure 2 Wherein, Mn, Ni, Co, and Se are element distribution diagrams of element Mn, element Ni, element Co, and element Se, respectively;
[0030] Figure 3 The preparation method of the lithium-rich manganese-based material having a spinel @Na2SeO3 structure of the present invention, the microstructure diagram of Example 3; Figure 3 (a) is the HR-TEM image of NSO-0. Figure 3 b is the FFT image of NSO-0. Figure 3 (c) is the HR-TEM image of NSO-3%. Figure 3 (d) is the FFT image of NSO-3%;
[0031] Figure 4 The preparation method of the lithium-rich manganese-based material having a spinel@Na2SeO3 structure of the present invention, the XPS graph of each sample in Example 3; Figure 4a in the figure is the Mn 2p spectrum, Figure 4 b is the Ni 2p spectrum, Figure 4 In the figure, c is the Co 2p spectrum. Figure 4 In the figure, d is the O1s spectrum. Figure 4 The middle e is the full spectrum, Figure 4 In the figure, f is the Se 3d spectrum;
[0032] Figure 5 The preparation method of the lithium-rich manganese-based material having a spinel@Na2SeO3 structure of the present invention, the electrochemical performance analysis diagram of Example 4; Figure 5 a is the initial charge and discharge curve, Figure 5 b is the first cycle cyclic voltammetry curve at 0.1mV / s. Figure 5 c is the rate performance diagram at 0.1-10C, Figure 5 The average voltage decay curve under 1C is shown in d. Figure 5 e in the figure is the cycle curve at 0.5C. Figure 5 f in the middle is the cycle curve under 1C;
[0033] Figure 6 The preparation method of the lithium-rich manganese-based material having a spinel@Na2SeO3 structure of the present invention, the kinetic test diagram of Example 5; Figure 6 a in the figure is the EIS graph of each sample. Figure 6 b is Z under low-frequency electrochemical impedance spectroscopy w and ω -1 / 2 The relationship diagram between . DETAILED DESCRIPTION
[0034] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0035] The preparation method of the lithium-rich manganese-based material with a spinel @Na2SeO3 structure of the present invention comprises mixing and grinding the lithium-rich manganese-based positive electrode material with sodium selenite, and calcining under an argon environment to obtain the lithium-rich manganese-based material with a spinel @Na2SeO3 structure.
[0036] The preparation method of the lithium-rich manganese-based material with a spinel @Na2SeO3 structure of the present invention comprises mixing sodium selenite with a lithium-rich manganese-based positive electrode material and calcining the mixture to make the Se on the surface of Na2SeO3 4+ A reduction reaction occurs, initiating the Mn 4+ Reduced to Mn 3+ , Mn 3+The appearance of Na2SeO3 induces the formation of a layer of spinel structure on the surface of the material, and finally obtains a lithium-rich manganese-based material with a spinel@Na2SeO3 structure. Na2SeO3 coating can enhance the structural stability of the material surface, thereby reducing structural rearrangement during charging and discharging.
[0037] The preparation method of the invention has the advantages of simple steps, mild reaction conditions, low preparation cost and good coating effect.
[0038] The preparation method of the present invention can obtain Li with an in-situ spinel phase and a Na2SeO3 coating layer. 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 materials. The Na2SeO3 coating can generate abundant oxygen vacancies on the surface of the material, effectively inhibiting the unstable oxygen release during the cycle and protecting the active material from corrosion by the electrolyte. As an in-situ spinel phase, it can provide a three-dimensional lithium ion transmission channel, thereby effectively accelerating the transmission of lithium ions.
[0039] Preferably, in the preparation method of the present invention, the calcination temperature is 330° C. to 370° C., and the calcination time is 2 to 4 hours.
[0040] More preferably, the calcination temperature is 350° C. and the calcination time is 3 h.
[0041] Preferably, based on 100wt% of the total mass after mixing, the mass percentage of sodium selenite is 1wt% to 4wt%.
[0042] Further preferably, the mass percentage of sodium selenite is 3wt%.
[0043] More preferably, the lithium-rich manganese-based positive electrode material is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 material (LMR material).
[0044] The Li of the present invention 1.2 Mn 0.54 Ni 0.13 Co 0.13 The preparation method of O2 material is a co-precipitation-high temperature solid phase method, which includes the following steps:
[0045] S1, preparation containing Mn 2+ 、Ni 2+ 、Co 2+ A mixed sulfate solution, a Na2CO3 solution and an ammonium bicarbonate aqueous solution; wherein the Mn 2+ 、Ni 2+ 、Co2+ The molar ratio is 54:13:13, the total cation concentration is 2 mol / L, the concentration of Na2CO3 solution is 2 mol / L, and the concentration of ammonium bicarbonate aqueous solution is 0.12 mol / L.
[0046] S2. Inject the mixed sulfate solution and Na2CO3 solution into the preheated ammonium bicarbonate aqueous solution at the same time, stir and react, and after the reaction is completed, let it stand and age to obtain a product; the feed rate of the mixed sulfate solution and Na2CO3 solution is 0.5 mL / min.
[0047] Preferably, the stirring rate is 800-1200 rpm / min, the pH value of the reaction solution is 8, and the reaction time is 15-17 h.
[0048] Preferably, the preheating temperature is 53°C to 57°C.
[0049] Preferably, the temperature for static aging is 55° C. and the time is 12 h.
[0050] S3. Filter, separate, wash and dry the product in sequence to obtain carbonate precursor powder.
[0051] S4, mixing and grinding the precursor powder and lithium carbonate, wherein the molar ratio of the precursor powder to the lithium carbonate is 1:1.35; then pre-calcining and high-temperature calcining are performed in sequence to obtain Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 material; the pre-sintering temperature is 550℃~650℃, the time is 4~6h, and the high temperature calcining temperature is 850~950℃, the time is 10~12h.
[0052] The lithium-rich manganese-based material with a spinel@Na2SeO3 structure of the present invention is prepared by the above-mentioned method.
[0053] The lithium-rich manganese-based material of the present invention can improve the electrochemical performance of the LRM positive electrode material after being coated with Na2SeO3. This is attributed to the synergistic effect produced by the stability of the reduction-induced electrochemically active spinel intermediate layer and the material surface coating layer. The stability of the material surface structure is improved after coating modification.
[0054] Preferably, the LMR material modified with 3wt% Na2SeO3 exhibits better electrochemical performance, and its discharge capacity and initial coulombic efficiency can reach 285.5mAhg -1 and 84.6%; the capacity retention rates after 200 cycles at 0.5C and 1C rates are 86.4% and 68.5% respectively; the specific capacity at 10C rate is 87.4 mAh g -1; The voltage drop after 200 cycles is 0.4445V.
[0055] The present invention is described below by means of specific examples.
[0056] Example 1 Preparation of lithium-rich manganese-based materials with different Na2SeO3 coating amounts
[0057] This embodiment adopts the method of the present invention to prepare a lithium-rich manganese-based material having a spinel@Na2SeO3 structure, and the specific preparation process is as follows:
[0058] Preparation of Li by co-precipitation combined with high temperature solid phase method 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 material.
[0059] First, according to Mn 2+ :Ni 2+ :Co 2+ In a molar ratio of 54:13:13, 4.5g MnSO4, 1.86g CoSO4 and 1.73g NiSO4 were weighed respectively, added into 20mL deionized water, and ultrasonically dissolved to obtain a mixed sulfate solution with a total cation concentration of 2mol / L; 4.25g Na2CO3 was weighed and added into 20mL deionized water to obtain a 2mol / L Na2CO3 solution; 20mL of 0.12mol / L ammonium bicarbonate aqueous solution was prepared, injected into a round-bottom flask, and heated to 55℃ in an oil bath for standby use.
[0060] Secondly, the mixed sulfate solution and Na2CO3 solution were simultaneously injected into the preheated ammonium bicarbonate solution at a feed rate of 0.5 mL / min using a syringe pump. During the reaction, the solution stirring rate was maintained at 1000 rpm / min and the pH value was 8 to ensure that the nucleation and growth rates of the particles were basically consistent. After the feeding was completed, the reaction was continued for 16 hours. After the reaction was completed, it was aged at 55°C for 12 hours.
[0061] Subsequently, the aged sample was filtered and separated, and washed with a large amount of deionized water and ethanol solution (to remove Na + NH 4 + and SO4 2- The cleaned sample was placed in a vacuum drying oven for drying at 80°C for 24h to obtain a light pink carbonate precursor powder.
[0062] Finally, the precursor powder was mixed and ground with lithium carbonate (the molar ratio of precursor: lithium carbonate was 1:1.35), and the mixed sample was pre-burned at 600°C for 5h in a tube furnace and then calcined at 900°C for 12h to obtain a lithium-rich manganese-based positive electrode material, which was labeled as LRM.
[0063] Sodium selenite (Na2SeO3) and LRM powders with mass fractions of 1wt%, 2wt%, 3wt% and 4wt% were ground in a mortar for 1h, and then the obtained solid mixture was calcined at 350℃ for 3h in an argon environment. 4+ A reduction reaction occurs, causing Mn 4+ Reduced to Mn 3+ . Mn 3+ The appearance of induced a layer of spinel structure to form on the surface of the material. Finally, a lithium-rich manganese-based material with spinel@Na2SeO3 structure was obtained.
[0064] According to different coating amounts of Na2SeO3, the materials prepared in this example are marked as NSO-1%, NSO-2%, NSO-3% and NSO-4%, respectively.
[0065] Example 2 Lattice structure analysis of lithium-rich manganese-based materials with different Na2SeO3 coating amounts
[0066] In this example, XRD was used to test the lattice structures of the NSO-1%, NSO-2%, NSO-3% and NSO-4% samples prepared in Example 1. At the same time, for better comparison, the LRM without Na2SeO3 coating, denoted as NSO-0, was also tested. The results are shown in FIG. Figure 1 As shown in a.
[0067] according to Figure 1 As can be seen in a, the five samples all have similar diffraction peaks, which can be corresponded to the layered α-NaFeO2 component of the LiMO2 phase with R-3m symmetry. In addition, the weak peak between 20-23° belongs to the superlattice order peak of LiMn6 in the transition metal layer Li2MnO3 (C2 / m). In addition, a weak shoulder peak was found around the (101) peak of the NSO-3% and NSO-4% materials, indicating the presence of a spinel phase in the two materials. The formation of the spinel phase is attributed to the reduction reaction of Na2SeO3 in an argon atmosphere at 350°C, which triggers the Mn on the surface of the material. 4+ Reduced to Mn 3+ , thus causing the rearrangement of the surface structure, which can be verified by XPS analysis. It is worth noting that due to the small amount of Na2SeO3 coating, no characteristic peaks corresponding to Na2SeO3 were found.
[0068] Raman spectroscopy is a sensitive method to distinguish layered and spinel structures, such as Figure 1 The Raman spectra of NSO-0 and NSO-3% samples are shown in b, at 478 cm -1 and 590cm -1 The two main peaks at correspond to the E g and A 1g Vibration mode. 430cm -1 A faint broad peak at represents the A phase of Li2MnO3 g Vibration model (C2 / m). In addition, compared with NSO-0, NSO-3% has a -1 There is a weak shoulder peak at the center, which is attributed to the Mn-O vibration of the MnO6 octahedron in the spinel structure (Fd-3m). This further confirms the existence of the spinel phase after the surface modification of Na2SeO3.
[0069] Example 3 Micromorphology Analysis of Li-rich Manganese-based Materials with Different Na2SeO3 Coating Amounts
[0070] In this example, the microscopic morphologies of the NSO-1%, NSO-2%, NSO-3% and NSO-4% samples prepared in Example 1 were analyzed. At the same time, for better comparison, the LRM without Na2SeO3 coating, denoted as NSO-0, was also compared.
[0071] Figure 2 aj in the figure are SEM images of NSO-0, NSO-1%, NSO-2%, NSO-3% and NSO-4% samples respectively; all five samples are composed of secondary microspheres (5-6um) formed by primary nanoparticles (200-300nm), indicating that the coating layer does not affect the morphology and size of the LRM material. And as the coating amount increases, the Na2SeO3 coating layer on the surface of the material gradually becomes denser. In addition, EDS is used to detect the presence of the Na2SeO3 coating layer, and the corresponding element distribution diagram is shown in the figure. Figure 2 The element distribution diagram of K and Mn, Ni, Co and Se is shown in the figure. The uniform distribution of Se element indicates that the Na2SeO3 coating layer has been successfully coated on the surface of LRM particles.
[0072] In order to further study the microstructure of LRM materials, two representative materials, NSO-0 and NSO-3%, were tested by TEM. The test results are shown in Figure 3 shown.
[0073] according to Figure 3 As can be seen in Figure a, NSO-0 exhibits clear lattice fringes with a spacing of 0.472nm, corresponding to the (003) plane of the layered structure. Figure 3As can be seen in Figure b, there are obvious lattice fringes inside NSO-3%, with a spacing of 0.472nm, and the lattice spacing in the middle transition zone is 0.237nm, which is related to the (222) crystal plane of the spinel-like structure. In addition, the outer layer is coated with an amorphous layer with a thickness of about 2-3nm. In order to determine the element distribution of the amorphous layer, as above Figure 2 In addition to Ni, Co and Mn, Se was also confirmed to be uniformly distributed on the surface of the material, indicating that the covering layer may be amorphous Na2SeO3. Based on the above test results, the LRM layered@spinel@Na2SeO3 structure was successfully obtained through a simple coating strategy.
[0074] Furthermore, this example uses XPS testing to explore the surface chemical states of NSO-0, NSO-1%, NSO-2%, NSO-3% and NSO-4%, such as Figure 4 As shown. Figure 4 In a, the peaks at 641.9 eV and 642.8 eV in NSO-0 correspond to the Mn 2p3 / 2 3+ and Mn 4+ After coating modification, NSO-3% Mn 3+ / Mn 4+ The content ratio of NSO-0 is larger than that of NSO-0, indicating that the Mn 4+ Reduction to Mn 3+ , which is related to the formation of spinel phase. Figure 4 As shown in b, the Ni 2p spectra of the two samples can be divided into two peaks located at 854.91 and 856.26 eV, corresponding to Ni 2+ and Ni 3+ After Na2SeO3 coating, the peak position of Ni 2p spectrum did not change significantly, indicating that the valence state of Ni was stable. Figure 4 As shown in Figure c, the 2p3 / 2 peak of Co in NSO-0 is at 780.06eV, and the 2p1 / 2 peak is at 795.54eV, indicating that the oxidation state of Co is +3, and the valence state of Co in NSO-3% has not changed significantly. Figure 4 As shown in the O1s spectrum in d, the surface modification process of NaSeO3 can produce more oxygen vacancies in the LMR material. The O1s spectrum shows two obvious characteristic peaks near 529.3eV and 530.8eV, corresponding to lattice oxygen (OMO) and oxygen vacancies, respectively. From the fitting results of the XPS spectrum, the proportion of oxygen vacancies in the NSO-3% sample is higher than that in the NSO-0 sample due to the formation of the spinel phase. In addition, as Figure 4As shown in Figure 5, in the Se 3d XPS spectrum of the NSO-3% sample, there is an obvious peak related to the Se element at 53.7 eV. Combined with other analysis results, it can be further proved that Na2SeO3 was successfully introduced into NSO-3%.
[0075] Example 4 Analysis of electrochemical properties of lithium-rich manganese-based materials with different Na2SeO3 coating amounts
[0076] The electrochemical behavior of LRM materials during the initial cycle is highly dependent on the redox activity of oxygen anions, which plays a crucial role in the subsequent cycling performance of the material. Therefore, during the initial cycle at 0.1C, the typical charge-discharge curves of NSO-0, NSO-1%, NSO-2%, NSO-3%, and NSO-4% samples are as follows: Figure 5 As shown in a.
[0077] according to Figure 5 It can be seen that during charging, the slope below 4.5 V is attributed to Li + The removal of Ni from the LiMO2 component is also accompanied by 2+ / Ni 3+ / Ni 4+ and Co 3+ / Co 4+ The long platform above 4.5 V is related to the activation process of the Li2MnO3 component, which involves the oxidation of lattice oxygen and the irreversible loss of oxygen. In the discharge curve, it is worth noting that all Na2SeO3-modified LRMs have a platform below 3 V, which is attributed to the Li + inserted into the spinel phase, which indicates that the Na2SeO3 surface engineering induced the generation of the spinel phase.
[0078] In addition, at 0.1C rate, the first discharge capacity of the unmodified sample is 240.7 mAh g -1 , ICE is 73.7%. In comparison, the first discharge specific capacities of NSO-1%, NSO-2%, and NSO-3% are 249.9, 259.7, and 285.5 mAh g, respectively. -1 ; The improved ICEs are 73.8%, 75.1% and 79.4% respectively. These results indicate that Na2SeO3 coating can enhance the structural stability of the material surface, thereby reducing the structural rearrangement during the charge and discharge process.
[0079] However, the discharge specific capacity of NSO-4% is only 205.3 mAhg -1 , ICE is 45.9%. This decrease in electrochemical performance can be attributed to the fact that the excessive Na2SeO3 coating hinders the Li +Among various samples, NSO-3% exhibits the highest specific discharge capacity and ICE, indicating that appropriate surface treatment can enhance the electrochemical performance of LRM cathode materials, which is attributed to the synergistic effect of the reduction-induced stabilization of the electrochemically active spinel interlayer and the surface coating of the material.
[0080] Figure 5 b is the first cycle cyclic voltammetry curve of the original LMR and the modified sample after Na2SeO3 coating. It can be seen from the figure that the four samples have similar CV curves in the first cycle, where the oxidation peak at 4V corresponds to the transition metal (Ni 2+ / 4+ and Co 3+ / 4+ ), and the oxidation peak at 4.5V belongs to the activation of Li2MnO3 component. In addition, all the redox peaks in the first cycle CV curves of the four samples almost overlap, indicating that the stability of the surface structure of the material is improved after coating modification.
[0081] In order to further explore the effect of the spinel@Na2SeO3 coating structure on the LRM material, the cycling performance and rate performance at high current density of NSO-0, NSO-1%, NSO-2%, NSO-3% and NSO-4% samples were tested at 0.5C and 1C between 2.0-4.8V. The rate performance of the five samples at 0.1C to 10C is shown in Figure 2. Figure 5 Obviously, NSO-3% exhibits excellent rate performance compared with other samples, and the discharge capacities at 0.1-10C are 276.6, 255.8, 239.2, 222.2, 184.4, 139.5 and 87.4 mAh g, respectively. -1 The excellent rate performance is due to the spinel structure with three-dimensional diffusion channels, which is beneficial to improve the Li + The transmission rate.
[0082] like Figure 5 As shown in e and 5f, after 200 cycles, the NSO-3% sample showed the best cycle stability, with a discharge capacity of 185.3 mAh g after 200 cycles at 1C. -1 The capacity retention rate is 78.5%; the specific capacity after cycling at 0.5C is 221.6 mAh g -1 , the capacity retention rate is 86.4%. This is because the reduction-induced spinel structure has a stable 3D skeleton and has good structural compatibility with the layered phase, which can increase the structural stability and further inhibit the phase transition. Moreover, the outermost Na2SeO3 layer can stabilize the electrode surface structure and reduce the reaction between the active material and the electrolyte. Therefore, the synergistic effect of the Na2SeO3 protective layer and the spinel structure contributes to the improvement of the cycle performance.
[0083] Voltage decay is another challenge faced by LRM materials due to the irreversible lattice oxygen loss-induced phase transition. Figure 5 d is the voltage decay curve of all samples at 1C current density. It can be observed that NSO-0 has a severe voltage decay of 0.6995V after 200 cycles. In contrast, the voltage decay of the Na2SeO3 modified sample is significantly suppressed, especially the NSO-3% sample, which has a voltage drop of only 0.4445V after 200 cycles. The alleviation of voltage decay can be attributed to the fact that the oxygen vacancies on the surface of the modified material hinder the release of lattice oxygen and improve the structural stability of the material, thereby hindering TM migration and the structural transformation of the layered phase to the spinel phase.
[0084] Example 4 Kinetic test of lithium-rich manganese-based materials with different Na2SeO3 coating amounts
[0085] In order to further understand the electrochemical performance of NSO-3% material, this example conducted EIS test on each sample. Figure 6 Nyquist plots of NSO-0, NSO-1%, NSO-2%, NSO-3% and NSO-4% after 3 cycles and Z' versus ω -1 / 2 Linear simulation diagram of the experimental data Figure 6 The equivalent circuit shown in (a) is simulated, and the corresponding results are shown in Table 1.
[0086] According to the experimental results, it can be seen that the Rs and Rct values of NSO-3% are lower than those of other samples. This is due to the protective effect of the Na2SeO3 coating layer, which isolates the active material from the organic electrolyte and inhibits the occurrence of side reactions.
[0087] Lithium ion diffusion coefficient (D Li+ ) can be calculated according to formula (1):
[0088]
[0089] according to Figure 6 The linear simulation shown in (b) calculates the D values of NSO-0, NSO-1%, NSO-2%, NSO-3% and NSO-4%. Li+ The values are 9.527×10 -16 , 1.550×10 -14 1.070×10 -14 , 1.180×10 -14 and 10.477×10 - 16 cm 2 s -1The excellent diffusion kinetics of NSO-3% is attributed to the fast lithium ion diffusion channels provided by the spinel structure. These results provide a good explanation for the excellent electrochemical performance of the NSO-3% sample, especially the excellent rate capability.
[0090] Table 1 Impedance fitting values and Li of NSO-0, NSO-1%, NSO-2%, NSO-3% and NSO-4% samples + Diffusion coefficient
[0091]
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure, characterized in that: The lithium-rich manganese-based positive electrode material is mixed with sodium selenite and ground, and then calcined under an argon environment to obtain the lithium-rich manganese-based material with a spinel@Na2SeO3 structure.
2. The method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure according to claim 1, characterized in that: The calcination temperature is 330° C. to 370° C., and the calcination time is 2 to 4 hours.
3. The method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure according to claim 1, characterized in that: Taking the total mass after mixing as 100wt%, the mass percentage of the sodium selenite is 1wt% to 4wt%.
4. The method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure according to any one of claims 1 to 3, characterized in that: The lithium-rich manganese-based positive electrode material is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 material.
5. The method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure according to claim 4, characterized in that: The Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 The preparation method of O2 material is co-precipitation-high temperature solid phase method.
6. The method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure according to claim 5, characterized in that: The coprecipitation-high temperature solid phase method comprises the following steps: S1, preparation containing Mn 2+ 、Ni 2+ 、Co 2+ A mixed sulfate solution, a Na2CO3 solution and an ammonium bicarbonate aqueous solution; wherein the Mn 2+ 、Ni 2+ 、Co 2+ The molar ratio is 54:13:13, the total cation concentration is 2 mol / L, the concentration of the Na2CO3 solution is 2 mol / L, and the concentration of the ammonium bicarbonate aqueous solution is 0.12 mol / L; S2, injecting the mixed sulfate solution and the Na2CO3 solution into the preheated ammonium bicarbonate aqueous solution at the same time, stirring and reacting, and after the reaction is completed, standing and aging to obtain a product; the feed rate of the mixed sulfate solution and the Na2CO3 solution is 0.5mL / min; the reaction time is 15 to 17h; S3, filtering, separating, washing and drying the product in sequence to obtain a carbonate precursor powder; S4, mixing and grinding the precursor powder and lithium carbonate, wherein the molar ratio of the precursor powder to the lithium carbonate is 1:1.35; then pre-calcining and high-temperature calcining are performed in sequence to obtain the Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 material; the pre-sintering temperature is 550℃~650℃, the time is 4~6h, the high temperature calcining temperature is 850~950℃, the time is 10~12h.
7. The method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure according to claim 6, characterized in that: In the step S2, the preheating temperature is 53°C to 57°C.
8. The method for preparing a lithium-rich manganese-based material having a spinel@Na2SeO3 structure according to claim 6, characterized in that: In the step S2, the temperature of the static aging is 55° C. and the time is 12 hours.
9. A lithium-rich manganese-based material having a spinel@Na2SeO3 structure, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It is prepared using the lithium-rich manganese-based material as claimed in claim 9.
Citation Information
Patent Citations
Spinel oxide coated lithium-rich manganese-based positive electrode material
CN113571679A
Lithium selenite / selenium dioxide double-layer coated ternary material and preparation method thereof
CN117813705A